Upaya Meningkatkan Kunjungan Wisatawan Ke Yogyakarta Melalui Promosi Wisata Budaya Di Anjungan Daerah Istimewa Yogyakarta Taman Mini “Indonesia Indah” - Rahasti Rengganingsih; Yulianto - AKPAR BSI Yogyakarta (Universitas Bina Sarana Informatika, 2012)
ABSTRACK - Efforts to increase tourist arrivals in the Pavilion area of Yogyakarta necessary and proper role of promotion in accordance with the development and progress of Yogyakarta. The analysis is based on theory and research in the field.The results showed that the pavilion Yogyakarta in Taman Mini